Enhancing Knowledge of Clinical Preceptors Towards Role Modeling Using Online Role Modeling Training - Lisa Musharyanti; Wulan Noviani; Jezyl Cempron Cutamora (Journal Of Nursing Practice, 2025)
Background: Role models play a significant role in shaping the character and professionalism of nursing students in clinical settings. Strengthening the impact of preceptors requires robust support and collaboration from educational institutions to ensure effective mentorship and professional development. Purpose: The aim of this study was to carry out role model training for clinical preceptors as an effort to increase knowledge their role as a role model in clinical education. Methods: This study employed a pre-experimental one group pretest-posttest design. A purposive sampling technique was used to recruit 33 clinical preceptors from six affiliated home-based hospitals. The training was conducted via Zoom  and included structured material presentations and small group discussions. Multiple-Choice Questionnaire were administered to participants in before  and after the last session of the training. Paired sample  t-test were used to analyze the mean differences of preceptors’ knowledge before and after the training. Results: The results showed that the majority of respondents demonstrated a good level of knowledge following the role modeling training, with 22 participants (66.7%) falling into the 'good knowledge' category, while only 1 participant (3.0%) remained in the 'poor knowledge' category. A statistically significant improvement was observed in the knowledge levels before and after the training, as indicated by p-value 0.000 (<0.05). Conclusion: Online role modeling training is an effective faculty-led initiative that has been proven to enhance clinical preceptors’ knowledge and awareness of their role as professional role models in clinical settings.